2017
DOI: 10.1680/jmacr.16.00424
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of early-age concrete reinforced with multi-walled carbon nanotubes

Abstract: The results of mechanical property tests on early-age concrete reinforced with industrial-grade carbon nanotubes (CNTs) are reported. The objective of the study was to validate the effectiveness of CNTs and establish the development of concrete properties with CNT dosage and concrete age. Ultrasonication, ultraviolet–visible spectrophotometry and scanning electron microscopy were employed to inspect or improve the dispersion quality. The test programme considered four CNT dosages and seven concrete ages, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The results of our previous research have shown that CNTs improve the flexural strength and deformation ability of UHSC [ 1 ]. Song et al [ 24 ] reported that CNTs lead to large increases in the tensile strength and ultimate strain of the concrete. Similar to CNTs, using GONSs with high specific surface areas might offer another approach to improving UHSC properties.…”
Section: Introductionmentioning
confidence: 99%
“…The results of our previous research have shown that CNTs improve the flexural strength and deformation ability of UHSC [ 1 ]. Song et al [ 24 ] reported that CNTs lead to large increases in the tensile strength and ultimate strain of the concrete. Similar to CNTs, using GONSs with high specific surface areas might offer another approach to improving UHSC properties.…”
Section: Introductionmentioning
confidence: 99%